Regulation of Type 2 Immunity in Myocardial Infarction - Xu, Jun-Yan; Xiong, Yu-Yan; Lu, Xiao-Tong; Yang, Yue-Jin (Frontiers in Immunology, 2019)
Type 2 immunity participates in the pathogeneses of helminth infection and allergic diseases. Emerging evidence indicates that the components of type 2 immunity are also involved in maintaining metabolic hemostasis and facilitating the healing process after tissue injury. Numerous preclinical studies have suggested regulation of type 2 immunity-related cytokines, such as interleukin-4, -13, and -33, and cell types, such as M2 macrophages, mast cells, and eosinophils, affects cardiac functions after myocardial infarction (MI), providing new insights into the importance of immune modulation in the infarcted heart. This review provides an overview of the functions of these cytokines and cells in the setting of MI as well as their potential to predict the severity and prognosis of MI.